Modelling Workforce Aging in Job Rotation Problems. Issue 3 (2015) - Boenzi, F.; Digiesi, S.; Mossa, G.; Mummolo, G.; Romano, V.A.
Abstract: Human factor is considered as a cost effective alternative to expensive automated solutions, as well as an easily interchangeable high flexible resource. However, for many years the influence of human behavior on production system performance has been underestimated and a lot of unrealistic assumptions have been used to simplify the human component modeling. Nowadays, population aging is acknowledged as a global trend. Among individual factors impacting on workers' performance, high attention is being paid to the age from scientific community, policy-makers and business leaders. In this paper, demographic aspects and their implications on workforce composition are illustrated; successively, main findings on age-related performance characteristics are summarized. The authors propose an age- related model which aims to find optimal job rotation schedules in work environments characterized by low load manual tasks with a high frequency of repetition (e.g. assembly lines). The model is an integer programming model allowing for the maximization of the overall system performance jointly reducing and balancing human workloads and ergonomic risk within acceptable limits. A numerical example is proposed.